Vein of Galen Aneurysmal Malformation in a Neonate: A Case Report - Ahmad Shah Farhat; Abbas Alizadeh Kaseb; Fatemeh Khorakian; Ashraf Mohammadzadeh; Reza Saeidi (Mashhad University of Medical Sciences, 2016)
Vein of Galen aneurysmal malformation (VGAM) is a rare congenital malformation, accounting for less than 1% of cerebrovascular abnormalities. The majority of reported cases have been associated with congestive heart failure (CHF) in the neonatal period. Herein, we present a case of VGAM, diagnosed at 37 weeks of gestation during the intrauterine life Case report: A full-term female newborn presented with severe CHF at two days of age. The patient's peripheral pulses were bounding in all four extremities. The first heart sound appeared to be normal, while the second had an accentuated pulmonic component. A systolic murmur (grade 3/6), best heard in the pulmonary area, was reported, and a cranial bruit was sought and found. The echocardiography showed evidence of right ventricular hypertrophy, while the chest X-ray indicated cardiomegaly with increased pulmonary vascularity. Moreover, echocardiography revealed dilation of the right heart chambers, a patent foramen ovale, severe tricuspid regurgitation, as well as a moderate-sized secundum atrial septal defect and a patent ductus arteriosus with right-to-left shunting. Transcranial ultrasound and contrast-enhanced CT scan of the brain detected a vein of Galen malformation. Magnetic resonance venography confirmed VGAM and identified the vessels feeding the aneurysm. Postnatal management included aggressive medical treatment of CHF. Transarterial embolization of the vessels feeding the aneurysm was suggested. However, the newborn succumbed to her disease on the following day. Conclusion: VGAM, which is a rare cause of cyanosis and heart failure in newborns, can be clinically diagnosed via proper strategies. However, extensive distribution of aneurysm usually precludes surgical management and endovascular treatment.